The tadpole of Physalaemus jordanensis Bokermann, 1967 (Anura, Leiuperidae) from Campos do Jordão, Serra da Mantiqueira, Southeastern Brazil - Gomes, Felipe Bittioli R.; Provete2, Diogo B.; Martins, Itamar A. (Zootaxa, 2010)
Physalaemus jordanensis was described by Bokermann (1967), based on specimens from “Lagoinha da Serra” (1500 m a.s.l.), Campos do Jordão, Serra da Mantiqueira, State of São Paulo, Brazil. Like other members of P. gracilis species group, presents a restricted geographical distribution (Nascimento et al. 2005), and after the 1980s, this species was no longer registered in the type locality. The species is assigned as "Data Deficient" in the Brazilian list of endangered species and the IUCN Red List (Nascimento & Verdade, 2004). Here we describe the tadpole of Physalaemus jordanensis from Campos do Jordão, State of São Paulo, Brazil, and compare it with the published morphological descriptions of the tadpoles belonging to the P. gracilis species group and sympatric species.